Learning Through Augmented Reality: The Indonesia Open University Experience - Kristina Anugerah Aji; Rijanto Purbojo (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
Augmented reality is a combination of the real dan virtual worlds that has an opportunity to be an integrated learning medium in online tutorial classes. The potential of augmented reality with multimedia capabilities creates an immersive learning environment. TPEN4314 Produksi Media/ TV course is a course that requires practice through augmented reality media for students in Open University specifically in the Educational Technology study program. This study aims to investigate the correlation between the experience of using augmented reality with student learning motivation, engagement, and acceptance of technology as well as the influence of the three variables on the experience of using augmented reality. The research method used quantitative with Likert Scale questionnaires and data analysis with multiple regression tests. The result of the analysis showed that there was a correlation between the variables of augmented reality experience and the three independent variables that affected the dependent variable. It is hoped that this research can contribute to tutors and learning media developers to design learning media that facilitate the independence of distance student learning to achieve the goal of competency in practical courses so that students get a meaningful learning experience.